Functional magnetic resonance imaging response as an early biomarker of cognitive decline in elderly patients with metabolic syndrome - Shigaeff, Nadia; Amaro, Edson; Franco, Fabio G. M.; Jacinto, Alessandro F. [UNESP]; Chiochetta, Gabriela; Cendoroglo, Maysa S.; Citero, Vanessa A. (Elsevier B.V., 2017)
Objectives: We assessed whether potential changes in brain activation patterns of elderly individuals with metabolic syndrome (MetS) who were cognitively healthy (without mild cognitive impairment or dementia) were associated with cognitive decline in executive function in the short-term. Method: We analyzed 43 individuals (23 MetS, 20 controls) using a global geriatric evaluation, a neuropsychological battery, and task-related (attention) fMRI exam. Correlation analysis between the fMRI signal at baseline and cognitive impairment after 1 year was based on the voxel-based Pearson coefficient, corrected for multiple comparisons. Results: At baseline, MetS patients showed reduced brain response in frontal and parietal regions compared to controls. After one year, the MetS group also showed a decline in verbal fluency performance. fMRI response in the right dorsolateral prefrontal cortex and bilateral parietal lobes was negatively correlated with verbal fluency decline in the MetS group. Discussion: Our results provide an early biomarker of the possible development of cognitive impairment, particularly in the executive function, of elderly individuals suffering from MetS. These findings also point to an up or down regulation which could be interpreted as compensatory mechanism for possible brain tissue burden caused by MetS.
Keywords: Metabolic syndrome; Elderly; Biomarker; Neuropsychological assessment; Cognitive impairment; Functional magnetic resonance